Common Pines of Florida - Niels Proctor; Martha C. Monroe (EDIS)
Pine trees are highly important to Florida’s ecosystems and economy. There are seven species of native pines, and each grows best in a particular environment. People have found varied uses for each species as well. Several species are of commercial value and are cultivated and managed to provide useful products such as paper, industrial chemicals, and lumber. Some species are also managed to enhance wildlife habitat and to provide attractive landscapes. Of course, many pines grow naturally. Like any natural resource, pines may provide more benefits if they are managed wisely. This 11-page fact sheet gives an overview of the features and identification of the major pines found in Florida. Written by Niels Proctor and Martha Monroe, and published by the School of Forest Resources and Conservation, April 2016.